Musculoskeletal modelling in sports - evaluation of different software tools with focus on swimming - Langholz, J. B.; Westman, G.; Karlsteen, M. (Procedia Engineering, 2016)
Previous swim start measurements at Chalmers University of Technology involved electromyography (EMG) in order to get an overall picture of the muscle activation pattern during the swim start. In order to fully evaluate sports performance trainers may facilitate additional tools, like videography and force plates, to be able to underpin the feedback given to the athletes. However, the output of the different tools are often complicated and lengthy to handle. Therefore it would be valuable to find an easily applicable tool to visualize biomechanical data. Feedback to athletes based on scientifically measured variables would then ideally be more efficient and effective. This paper evaluates three different software tools regarding musculoskeletal modelling and simulation with quick, meaningful and unambiguous data processing and presentation: OpenSim, BoB and AnyBody. The software package SWUM was also analyzed as it is currently the only tool that can model forces and buoyancy during swimming. It has been found that OpenSim is a beneficial tool for academic projects as it is freely available and provides a big pool of users and papers available to support the user with additional knowledge. BoB is the most straight-forward tool being appropriate for biomechanical teaching and applications where a fast analysis is required. AnyBody has the most sophisticated model which can be adjusted to the users demands in great detail and is favorable for investigations with focus on the interaction between the body and the environment or a detailed medical analysis. Great potential lies in the further development and usage of SWUM as its basic interface with valuable outputs and simulations as well as the possibility of connecting to AnyBody might allow for advancements in swim training.